2022
DOI: 10.13181/mji.oa.226118
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with global cognitive impairment in epilepsy patients: a cross-sectional study in Mataram, Indonesia

Abstract: BACKGROUND Cognitive impairment is a major complication of epilepsy. This study aimed to investigate the factors associated with the prevalence of cognitive impairment in patients with epilepsy in Mataram, Indonesia. METHODS This cross-sectional study involved 155 consecutive outpatients with epilepsy at Mataram General Hospital, Mutiara Sukma Mental Hospital, and Siti Hajar Hospital, Mataram, Indonesia between September 2017 and August 2020. Data on the patient’s demographic characteristics, epilepsy, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Educational level is another factor that affects the occurrence of cognitive impairment among epileptic patients; studies identified cognitive impairment is inversely associated with education level (Beh et al, 2020; Harahap et al, 2022; Wang et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Educational level is another factor that affects the occurrence of cognitive impairment among epileptic patients; studies identified cognitive impairment is inversely associated with education level (Beh et al, 2020; Harahap et al, 2022; Wang et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This evaluation aims to guide diagnostic ceonsiderations, treatment initiation, and administration of anti-seizure medications to reduce the life-threatening effects of prolonged seizures and status epilepticus, 3 as well as global cognitive impairment. 4 The first seizure episode is a life-changing event with psychophysical consequences. 5 Patients must be appropriately assessed and managed immediately after an unprovoked seizure.…”
mentioning
confidence: 99%